Receptor tyrosine kinase amplification is predictive of distant metastasis in patients with oral squamous cell carcinoma. Issue 2 (February 2017) - Oikawa, Yu; Morita, Kei‐ichi; Kayamori, Kou; Tanimoto, Kousuke; Sakamoto, Kei; Katoh, Hiroto; Ishikawa, Shumpei; Inazawa, Johji; Harada, Hiroyuki
Abstract : This study aimed to clarify the genomic factors associated with the diagnosis and prognosis of oral squamous cell carcinoma via next‐generation sequencing. We evaluated data from 220 cases of oral squamous cell carcinoma. Genomic DNA was eluted using formalin‐fixed, paraffin‐embedded samples, and targeted resequencing of 50 cancer‐related genes was performed. In total, 311 somatic mutations were detected in 220 patients, consisting of 68 synonymous mutations and 243 non‐synonymous mutations. Genes carrying mutations included TP53, CDKN2A, and PIK3CA in 79 (35.9%), 35 (15.9%), and 19 patients (8.6%), respectively. Copy number analysis detected amplification of PIK3CA and AKT1 in 38 (17.3%) and 11 patients (5.0%), respectively. Amplification of receptor tyrosine kinases was found in 37 patients (16.8%). Distant metastasis was noted in nine of 37 patients (24%) with receptor tyrosine kinase amplification, accounting for 43% of the 21 cases of distant metastasis. The cumulative 5‐year survival rate was 64.6% in the receptor tyrosine kinase amplification group vs 85.2% in the no receptor tyrosine kinase amplification group. Moreover, we identified significantly poorer prognosis in the TP53 mutation/receptor tyrosine kinase amplification group, for which the cumulative 5‐year survival rate was 41.6%. In conclusion, the results of this study demonstrated that receptor tyrosine kinase amplification is a prognostic factor for distant metastasis of oral squamous cell carcinoma, indicating the necessity of using next‐generation sequencing in clinical sequencing. Abstract : We evaluated data from 220 cases of oral squamous cell carcinoma. Targeted resequencing of 50 cancer‐related genes was performed. Receptor tyrosine kinase amplification is a prognostic factor for distant metastasis of oral squamous cell carcinoma, indicating the necessity of using next‐generation sequencing in clinical sequencing.